The total money makeover : a proven plan for financial fitness - Ramsey, Dave. (Nashville, Tenn. : Thomas Nelson Pub., 2009)
"Ramsey offers a bold, no-nonsense approach to money matters, providing not only the how-to but also a grounded and uplifting hope for getting out of debt and achieving total financial health. Ramsey debunks the many myths of money (exposing the dangers of cash advance, rent-to-own, debt consolidation) and attacks the illusions and downright deceptions of the American dream, which encourages nothing but overspending and massive amounts of debt. "Don't even consider keeping up with the Joneses," Ramsey declares in his typically candid style. "They're broke!" This book isn't theory. It works every single time. It works because it is simple. It works because it gets to the heart of the money problems: you"--Publisher's description.
Introduction: What this book is NOT -- Flying turkeys and skinny dipping -- The total money makeover challenge -- Denial: I'm not that out of shape -- Debt myths: the (non)secrets of the rich -- Two more hurdles: ignorance and keeping up with the Joneses -- Save {dollar}1,000 fast: walk before you run -- The debt snowball: lose weight fast, really -- Finish the emergency fund: kick Murphy out -- Maximize retirement investing: be financially healthy for life -- College funding: make sure the kids are fit too -- Pay off the home mortgage: be ultrafit -- Build wealth like crazy: Arnold Schwarzedollar, Mr. Universe of money -- Live like no one else -- Meet the winners of the Total Money Makeover Challenge -- Budgeting forms.
"Revised 3rd edition"--Jacket.
Includes index.
Keywords: Finance, Personal; Debt